A case study of a successful Olympic coach`s perspectives - Wang, J. (International Journal of Sport Studies, 2014)
In the competitive sport arena, coaches and researchers are continuously seeking successful coaching experiences for preparing athletes to achieve peak performance in the Olympic Games. In the past, some researchers have investigated the unique characteristics of the coaching approaches of a single successful coach; this is referred to as a single case study. Barker, McCarthy, Jones, and Moran (2001) indicated that single case research is a powerful method for helping us understand the development of more effective performance techniques for athletes and sports people in clinical populations. Thus, the purpose of this study is: (a) to investigate a Chinese Olympic table tennis legendary coach`s leadership style of coaching; (b) to reveal the participant`s particular coaching approaches; (c) to examine the participant`s successful experiences of coaching the Olympic teams; and (d) to reveal the major secrets of the participant`s winning formula. The attempt of the current study was to promote the exchange of new ideas in coaching and introduce the successful experiences of a world -class legendary coach to the coaching and research communities. Also, such a research endeavor helps to make a connection between the coaching and research professions.